Polarized infrared reststrahlen features of wurtzite ingan thin film - Yew, P.; Lee, S.C.; Ng, S.S.; Yoon, T.T.; Haslan, A.H.; Wei, L.C. (2014)
Polarized infrared (IR) reflectance measurement was carried out to investigate the optical phonon modes of wurtzite structure Ino.92GaoosN thin film grown by molecular beam epitaxy· Composition dependence of IR reststrahlen features was observed. Theoretical polarized ~ reflectance spectrum was simulated using the standard multilayer optics technique with a multloscillator dielectric function model. By obtaining the best fit of experimental and theoretical spectrum, the Brillouin zone center E, optical phonon modes together with the dielectric constant, layer thickness, free carriers concentration and mobility were extracted non-destructively. The extracted EI optical phonon modes were compared with those generated from modified random element iso-displacement (MREI) model.